Palmitic acid-coated magnetite nanocubes with high-quality crystallinity and bulk-like magnetic features - Orozco Henao, Juan Manuel (2020)
We have demonstrated the synthesis of high-quality monocrystalline magnetite nanocubes through the introduction of palmitic acid as surfactant in a thermal decomposition synthesis of an organic Fe precursor. Unlike the standard thermal decomposition synthesis route, we report the avoid of the reducing agent and a modification in the synthesis heating ramp. Structural and magnetic properties were investigated showing well defined cubic shaped nanoparticles with a backsim40nm edge and magnetic features close to bulk magnetite. We associate the bulk-like magnetic performance and properties to the highly crystalline structure of the nanocubes.